Genetic Analysis of the Salmonella FliE Protein That Forms the Base of the Flagellar Axial Structure - Hendriksen, Jordan J.; Lee, Hee Jung; Bradshaw, Alexander J.; Namba, Keiichi; Chevance, Fabienne F. V.; Minamino, Tohru; Hughes, Kelly T. (mBio, 2021)
The FliE component of the bacterial flagellum is the first protein secreted through the flagellar type III secretion system (fT3SS) that is capable of self-assembly into the growing bacterial organelle. The FliE protein plays dual roles in the assembly of the Salmonella flagellum as the final component of the flagellar type III secretion system (fT3SS) and as an adaptor protein that anchors the rod (drive shaft) of the flagellar motor to the membrane-imbedded MS-ring structure. The FliE component of the bacterial flagellum is the first protein secreted through the flagellar type III secretion system (fT3SS) that is capable of self-assembly into the growing bacterial organelle. The FliE protein plays dual roles in the assembly of the Salmonella flagellum as the final component of the flagellar type III secretion system (fT3SS) and as an adaptor protein that anchors the rod (drive shaft) of the flagellar motor to the membrane-imbedded MS-ring structure. This work has identified the interactions between FliE and other proteins at the inner membrane base of the flagellar machine. The fliE sequence coding for the 104-amino-acid protein was subject to saturating mutagenesis. Single-amino-acid substitutions were generated in fliE , resulting in motility phenotypes. From these mutants, intergenic suppressor mutations were generated, isolated, and characterized. Single-amino-acid mutations defective in FliE function were localized to the N- and C-terminal helices of the protein. Motile suppressors of amino acid mutations in fliE were found in rod protein genes flgB and flgC , the MS ring gene, fliF , and one of the core T3SS genes, fliR . These results support the hypothesis that FliE acts as a linker protein consisting of an N-terminal α-helix that is involved in the interaction with the MS ring with a rotational symmetry and a C-terminal coiled coil that interacts with FliF, FliR, FlgB, and FlgC, and these interactions open the exit gate of the protein export channel of the fT3SS. IMPORTANCE The bacterial flagellum represents one of biology’s most complex molecular machines. Its rotary motor spins at speeds of more than 2,000 cycles per second, and its type 3 secretion (T3S) system secretes proteins at rates of tens of thousands of amino acids per second. Within the complex flagellar motility machine resides a unique protein, FliE, which serves as an adaptor to connect a planar, inner membrane-embedded ring structure, the MS-ring, the core T3S secretion complex at the cytoplasmic base, and a rigid, axial structure that spans the periplasmic space, penetrates the outer membrane, and extends 10 to 20 microns from the cell surface. This work combines genetic mutant suppressor analysis with the structural data for the core T3S system, the MS-ring, and the axial drive shaft (rod) that transverses the periplasm to provide insight into the essential adaptor role of FliE in flagellum assembly and function.